Perlindungan Hukum Terhadap Hak Masyarakat Dalam Perjanjian Kerjasama Perkebunan Kelapa Sawit - Hamdan Siregar (Nagari Law Review, 2019)
The State of the Republic of Indonesia is a legal state which is contained in Article 1 Paragraph (3) of the 1945 Constitution, in the rule of law, the power in running the Government based on the rule of law, in Indonesia there have been many cooperation agreements in the field of plantation, in the establishment of plantation based on the principle legal certainty to protect the parties in the cooperation agreement between BUMD and PT.MTL where in the plantation management agreement is not running smoothly, causing conflict between the community with PT.MTL party. Based on the above issues, what is the legal relationship between the parties in the oil palm plantation cooperation agreement, how is the legal effect on the community rights in the oil palm plantation cooperation agreement, how is the legal protection of the community within the palm oil plantation agreement. This research is juridical sociological with the nature of research is descriptive analytical. Processing is done by editing and then analyzed by using qualitative analysis methode. From the result of the research, it can be concluded that (1) the occurrence of civil relation between the parties based on the cooperation agreement between BUMD and PT.MTL and letter of land delivery between the community and BUMD (2) due to law on community land in this cooperation agreement the transition of rights, from public property rights to State land. (3) the absence of legal protection of community land that has been submitted to the BUMD to be granted the Right to Use Enterprises